The Effect of TPA on In-Hospital Mortality in Patients Hospitalized with Ischemic Stroke in Florida from 2008-2012 - Bin Shihah, Abdulelah Saleh; Al Rushud, Abdullah F.; Aldaham, Sami A. (Integrative Journal of Medical Sciences, 2017)
Introduction. In the U.S., tissue Plasminogen Activator (tPA) is the only approved thrombolytic drug to re-canalize occluded arteries in patients with acute ischemic stroke (AIS). With timely administration, tPA may improve the patient’s prognosis. The percentage of AIS patients that receive tPA in the U.S., however, varies from 3.0% to 8.5%. Further, there is scarce information on the impact of tPA and short-term mortality among Floridians hospitalized with AIS. This study investigates factors associated with in-hospital mortality among patients admitted to Florida hospitals with AIS who received tPA compared to those who did not receive the thrombolytic. Methods. This is a secondary analysis of the Florida Stroke Registry for 2008-2012. We assessed the association between tPA administration and in-hospital mortality utilizing logistic regression to estimate unadjusted and adjusted odds ratios. Pearson correlation coefficients were used to diagnose collinearity. Results. A total of 133,052 ischemic stroke patients (51.9% women, average age 71.7±14.4 years) comprised our study sample. Approximately 5% (6,357) of AIS patients received tPA. After adjusting for potential confounders, AIS patients who received tPA were twice as likely to die than AIS patients not receiving tPA (OR=2.0; 95% CI= 1.8-2.2). AIS patients 90 years or older were five times more likely to die than AIS patients < 60 years (OR=5.0; 95% CI 4.4-5.7). Women were less likely to die compared to men (OR=0.9; 95% CI=0.87-0.99). Factors significantly increasing the likelihood of in-hospital mortality among AIS patients receiving tPA included being admitted to teaching hospitals (OR=1.6, 95% CI=1.5-1.7), lack of health insurance coverage (OR=2.0, 95% CI=1.8-2.3), extended hospitalization length of stay > 6 days (OR=1.2, 95% CI= 1.1-1.2), and not being assigned emergent priority at admission (OR=2.7, 95% CI= 2.5-2.9). Conclusion. Our findings suggest that the likelihood of in-hospital mortality among Floridian patients with AIS is twice as higher among those receiving tPA than those AIS patients not receiving the thrombolytic. Increasing age, being a man and admitted to a teaching hospital, lack of health insurance, extended length of stay, and not receiving emergent priority at admission also increased the likelihood of in-hospital death for AIS patients after receiving tPA.